A comparative study of the photochemistry of biphenyl adsorbed on cellulose and silicalite - J. P. Da Silva; L. F. Vieira Ferreira (International Journal of Photoenergy)
The photochemistry of biphenyl (BP) was studied on two model solid supports, silicalite and cellulose, using time resolved diffuse reflectance techniques and product degradation analysis. The results showed that the photochemical behaviour of BP depends on the solid support. Ground state absorption spectra indicated a near planar configuration in the ground state. BP triplet state was the only species detected on cellulose, while the radical cation (BP•+) was observed in silicalite. BP is relatively stable in both supports. Prolonged irradiations in cellulose lead to the formation of the three monohydroxybiphenyls, while in silicalite photooxidation products prevailed.